RELIGIOUS MODERATION TO PREVENT RADICALISM IN ACEH ISLAMIC COLLEGE : MODERASI BERAGAMA DALAM MENCEGAH RADIKALISME DI PERGURUAN TINGGI KEAGAMAAN ISLAM ACEH - Mawardi (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2022)
Aceh, which has had the privilege of implementing sharia law in its territory, has faced a major challenge for accusations of